1993
DOI: 10.1161/01.cir.88.6.2894
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical alternans in canine myocardium in vivo. Dependence on intracellular calcium cycling.

Abstract: Activation time is one of the factors modifying electrical alternans. Delayed intracellular Ca2+ cycling plays a role in the concomitant occurrence of electrical and mechanical alternans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 29 publications
5
69
0
Order By: Relevance
“…20,25,26,32 Results from the present study suggest that discordant alternans that arises by the second scenario could be prevented by drugs that increase conduction velocity or reduce range of DI over which conduction velocity varies, even if concordant alternans is not preventable.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…20,25,26,32 Results from the present study suggest that discordant alternans that arises by the second scenario could be prevented by drugs that increase conduction velocity or reduce range of DI over which conduction velocity varies, even if concordant alternans is not preventable.…”
Section: Discussionmentioning
confidence: 70%
“…[28][29][30] Two recent studies support primacy of APD alternans; activation times were identical from beat to beat. 31,32 Appearance of repolarization alternans at slower heart rate than depolarization alternans 8 also might be interpreted by some that conduction velocity is of lesser importance, although one would naturally expect repolarization (APD) alternans to occur at slower heart rates than depolarization (conduction velocity) alternans in normal cardiac tissue, because of the shorter DI at which conduction velocity varies. However, at the high pacing rates at which discordant alternans is seen, DI typically is small, and effects of conduction velocity cannot be separated from effects of repolarization.…”
Section: Discussionmentioning
confidence: 99%
“…That said, the model does not negate the importance of intracellular calcium concentration in determination of myocardial APD. Changes to intracellular calcium concentration affect APD restitution (24) and APD alternans (19,26,43). We conjecture that the calcium concentration determines APD restitution and accommodation and that the two can be measured and modeled decoupled from calcium concentration without consequence because they already encode the calcium concentration information.…”
Section: Modeling Results and Implicationsmentioning
confidence: 94%
“…During mechanical alternans, oscillations in contractile force are associated with oscillations in SR Ca 2ϩ release, and this alternans can be abolished by compounds such as caffeine (22) and ryanodine (15) that render the SR leaky to Ca 2ϩ . Ischemia and acidosis are known to facilitate the development of alternans (7,16) and to reduce the rate of SR Ca 2ϩ uptake (8), but 31 P NMR studies of failing SHHF and agematched WF rat hearts demonstrated no fall in intracellular pH with the induction of alternans (21). Moreover, as shown in a previous study, reducing the rate of SR Ca 2ϩ accumulation with thapsigargin does not decrease the threshold pacing frequency at which sustained mechanical alternans develops in healthy hearts (22).…”
Section: Discussionmentioning
confidence: 93%